Determinación de la influencia de las fases lunares, utilizando el calendario agrícola lunar, en tres variedades de fréjol (Phaseolus vulgaris L.) en el cantón Antonio Ante, provincia de Imbabura - Lahuasi Guerrero, Luis Fernando (2012)
The present investigation was made in the parish San Asleep, canton Antonio Before, county of Imbabura, using as material you siembra seeds of frejol varieties Paragachi,Canario and Yunguilla, coming from Santa Catalina (INIAP). The treatments were constituted by the fréjol varieties (Phaseolus vulgaris L) with the use of the lunar calendar, using the design blocks totally at random (DBCA) with six treatments and four repetitions whose variables were subjected to the variance analysis and to determine the statistical differences of multiple ranges the test of Tukey it was used. For the development of the experimental rehearsal they were carried out the following works as analysis of the floor, preparation of the floor, subscriber, siembra, fertilization, watering, control of overgrowths, control fitosanitario and cosecha. Para to estimate the effects of the treatments took the data like height from the plant to the 30, 60 and 90 days after the siembra, days to floración; days to maturation; longitude of sheaths; number of sheaths for plant; number of seeds for sheath; I weigh of 100 seeds; grain yield and economic analysis.